An Evaluation on Artificial Intelligence - Jigyasu, Diyani (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Artificial Intelligence is one of the best and most widely used tools in the modern era for data mining and data analysis. Sometimes it is also called machine intelligence. It is exhibited by machines. The effective AI models and algorithms are the best solutions to the various engineering and biological problems. According to father of artificial intelligence, john Mccarthy it is “the science and engineering of making intelligent machines, especially intelligent computer programs”. How to cite this article: Jigyasu D, Goyal N. An Evaluation on Artificial Intelligence. J Adv Res Appl Arti Intel Neural Netw 2020; 4(2): 3-5